Contributions of Yap and Taz dysfunction to breast cancer initiation, progression, and aging‐related susceptibility. Issue 1 (3rd July 2020) - Fresques, Tara; LaBarge, Mark A.
Abstract: Yap and Taz are co‐transcription factors that have been implicated in the development of many cancers. Here, we review the literature that analyzes the function of Yap/Taz in normal breast and breast cancer contexts. Our review of the literature suggests that Yap and Taz are involved in breast cancer and Taz, in particular, is involved in the triple‐negative subtype. Nevertheless, the precise contexts in which Yap/Taz contribute to specific breast cancer phenotypes remains unclear. Indeed, Yap/Taz dysregulation acts differentially and in multiple epithelial cell types during early breast cancer progression. We propose Yap/Taz activation promotes breast cancer phenotypes in breast cancer precursor cells. Further, Yap dysregulation as a result of aging in breast tissue may result in microenvironments that increase the fitness of breast cancer precursor cells relative to the normal epithelia.